2010
DOI: 10.1200/jco.2009.25.1082
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Visceral Metastases in Scottish Patients With BRCA1/2-Defective Ovarian Cancer: An Extension of the Ovarian BRCAness Phenotype

Abstract: Although sporadic EOC commonly remains confined to the peritoneum, BRCA1/2-deficient ovarian cancer frequently metastasizes to viscera. These data extend the ovarian BRCAness phenotype, imply BRCA1/2-deficient ovarian cancer is biologically distinct, and suggest that patients with visceral metastases should be considered for BRCA1/2 sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 24 publications
2
51
0
2
Order By: Relevance
“…Moreover, patients in this series could only access olaparib through clinical trials mainly (83%) involving resistant/partially sensitive disease, that is, patients with anticipated shorter OS. The median OS from initial diagnosis of 66.3 months for our patients lies within the range previously reported in observational studies of BRCA1/2-mutated patients with EOC before PARPi became available (29,30) and randomized trials will be required to properly assess the impact of olaparib on OS in BRCA1/2 mutation-associated EOC patients. In this context, a recently reported subgroup analysis of OS in the olaparib maintenance trial does suggest an OS benefit (HR of 0.74) for patients positive for germline and/or somatic BRCA1/2 mutations which was not evident in the overall population (HR of 0.88; ref 12,31).…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, patients in this series could only access olaparib through clinical trials mainly (83%) involving resistant/partially sensitive disease, that is, patients with anticipated shorter OS. The median OS from initial diagnosis of 66.3 months for our patients lies within the range previously reported in observational studies of BRCA1/2-mutated patients with EOC before PARPi became available (29,30) and randomized trials will be required to properly assess the impact of olaparib on OS in BRCA1/2 mutation-associated EOC patients. In this context, a recently reported subgroup analysis of OS in the olaparib maintenance trial does suggest an OS benefit (HR of 0.74) for patients positive for germline and/or somatic BRCA1/2 mutations which was not evident in the overall population (HR of 0.88; ref 12,31).…”
Section: Discussionmentioning
confidence: 55%
“…A recent meta-analysis of gene expression analyses has described a combination of biological markers that identified patients with suboptimal debulking [22]. Moreover, patients with BRCA1/2 mutation had a significantly higher risk of developing visceral metastases than matched controls without BRCA1/2 mutations [23]. Further work is warranted to clarify, whether tumor biology would help to identify those subgroups not suitable for upfront debulking surgery or even any surgery at all.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, HR-deficient cancers have a different phenotype and are often more sensitive to crosslinking agents including cisplatin than their HR-proficient counterparts (Bryant et al, 2005;Farmer et al, 2005;Ratnam and Low, 2007). For instance, BRCA1/2-deficient ovarian cancers metastasize to viscera more frequently than sporadic epithelial ovarian cancers (which most often remain confined to the peritoneum), yet are generally more responsive to platinum compounds and associated with better prognosis (Ben David et al, 2002;Chetrit et al, 2008;Gourley et al, 2010). Moreover, it has been shown that cisplatin resistance can develop in initially cisplatinsensitive tumors because of secondary mutations that compensate for BRCA1/2 deficiency and re-establish HR (Edwards et al, 2008;Sakai et al, 2008).…”
Section: Mlh1mentioning
confidence: 99%